LITTLE INNOVATIONS THAT MAKE A BIG IMPACT. Issue 108 (23rd March 2023) - Murray, Jill; Barone Pricci, Erica; Decker, Stephanie
Abstract: The authors, including Murray, the President of Lackawanna College in Scranton, Pennsylvania; write about innovation initiatives at the school, and their relevance to other organizations. They focus on what they call "Little Innovations, " described in their words as innovation born from necessity as an organization considers how to solve a central, pressing problem. They delineate five steps to little innovations, which in their words are: (1) Wild Questions: Why Can't We? (2) Practical Questions: How Can We? (3) Build a Team of Great Thinkers (4) Successful Failures (5) Follow Through. Step one has sub‐questions, such as "What if we re‐imagine the basic assumptions of our business?" In step two, "Think about how to break a big idea into its component parts and try it, taking care to create a timeline and assessment plan to figure out if the initiative is worth continuing or taking to a larger scale." In step three, "Without a culture of trust and a genuine belief in each other's brain power, free‐flowing conversations can't happen." In step four, "Share your failures and how they helped you pivot to the winning idea." And in step five, "An idea itself isn't an innovation until a leader or team can make it come to life and create tangible outcomes."